2019
DOI: 10.1177/2319714519843689
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Usage Intensity: Impact Assessment on Buyers’ Behavioural Traits

Abstract: With increasing proliferation of social media, there is an urgent need to examine how people engage in the social media as well as assess its role in shaping consumers' attitude and behaviour. Though the recent years have witnessed the interest of researchers in this regard, the studies have mostly been confined to analyzing the social media utilization patterns for their impact on online purchases and less emphasis has been laid on investigating its impact on the 'down side' of consumer behaviour as reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
0
9
0
6
Order By: Relevance
“…Contemporary digital channels have the capabilities to provide easy and quick access to digital content without altering the latter's configuration (Alghizzawi, 2019). Digital channels communication also offers customer and expert reviews that facilitate the product comparison and possibility of making an informed decision (Dahiya and Gayatri 2018;Gupta and Vohra, 2019) in their study confirmed that social media usage intensity positively and…”
Section: Introductionmentioning
confidence: 65%
“…Contemporary digital channels have the capabilities to provide easy and quick access to digital content without altering the latter's configuration (Alghizzawi, 2019). Digital channels communication also offers customer and expert reviews that facilitate the product comparison and possibility of making an informed decision (Dahiya and Gayatri 2018;Gupta and Vohra, 2019) in their study confirmed that social media usage intensity positively and…”
Section: Introductionmentioning
confidence: 65%
“…SMUI refers to the extent to which a user is emotionally attached to the platform and the degree to which the platform has been incorporated with the user's daily life (Ellison et al, 2007). Consistent with prior studies, SMUI can be operationalized by tapping into the attitudinal and feelings aspect of the user (Choi et al, 2018;Gupta and Vohra, 2019;Jordaan and Van Heerden, 2017).…”
Section: Social Media Usage Intensitymentioning
confidence: 89%
“…The study sample has been collected from social media pages of well-known e-commerce platforms, which frequently use heavily customized paid ads, also known as retargeting ads, whose negative effects on consumption and on the mental well-being of social media users have been reported in previous literature ( Lulandala, 2020 ). Thailand is among the most social media engaged population in the world having 51 million users on Facebook and 16 million users on Instagram, however, very little focus has been placed on investigating the characteristics of compulsive, impulsive and conspicuous consumption as effects of social media usage ( Gupta and Vohra, 2019 ).…”
Section: Introductionmentioning
confidence: 99%